2014
DOI: 10.1177/0193945914527521
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Rounds and Structured Communication Reduce Re-Admissions and Improve Some Patient Outcomes

Abstract: Hospital communication is more than access to information. Among staff, it is about achieving situation awareness-an understanding of a patient's current condition and likely trajectory. In the multidisciplinary context of providing care, structure, consistency, and repeatability of communication will enable a shared understanding of the patient and plan, leading to improved patient satisfaction and outcomes. This was tested using the Situation-Background-Assessment-Recommendation (SBAR) protocol, a re-admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 23 publications
2
48
0
Order By: Relevance
“…This study showed significant improvement in Foley catheter removal, reduction in re-admissions rate, and improvement in patient satisfaction. This study's results support the value of using SBAR during IDR to improve situational awareness and to maintain focus on relevant clinical issues (Table 1) [23].…”
Section: Sbar Communication Tool For Handoffsupporting
confidence: 72%
See 2 more Smart Citations
“…This study showed significant improvement in Foley catheter removal, reduction in re-admissions rate, and improvement in patient satisfaction. This study's results support the value of using SBAR during IDR to improve situational awareness and to maintain focus on relevant clinical issues (Table 1) [23].…”
Section: Sbar Communication Tool For Handoffsupporting
confidence: 72%
“…Despite huge investments in technology to record, store, disseminate, and access information, studies still find communication in health care continues to be problematic [23]. Health care providers need to be cognizant of the challenges facing handoffs, including physical setting, social setting, language barriers, and communication barriers [24].…”
Section: Challenges Of Communication In Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous studies have shown that improvements in hospital systems such as organizational culture, including interdisciplinary rounding during hospitalization and at discharge, and optimization of patient care transitions were associated with improved 30‐day outcomes 29, 30, 31. Similarly, other qualitative studies have shown that high‐performing hospitals have specific organizational strategies and enabling structures that distinguish them, including: active communication and coordination among care givers; senior management‐level engagement and support; and an organizational commitment to developing and maintaining a focus on delivering high‐quality care 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of publications pertaining to communication skills included verbal and nonverbal communication (Frankel et al, 2012), communicating with doctors (Donohue & Endacott, 2010), nursing handover (Cornell & Gervis, 2013;Cornell, Gervis, Yates, & Vardaman, 2014;De Meester, Verspuy, Monsieurs, & Van Bogaert, 2013;Radtke, 2013;Townsend-Gervis, Cornell, & Vardaman, 2014), the impact of different models of care on communication (Fernandez, Tran, Johnson, & Jones, 2010), communication technologies (Guarascio-Howard, 2011) and factors that impair communication (Johnson et al, 2014). The focus of publications pertaining to communication skills included verbal and nonverbal communication (Frankel et al, 2012), communicating with doctors (Donohue & Endacott, 2010), nursing handover (Cornell & Gervis, 2013;Cornell, Gervis, Yates, & Vardaman, 2014;De Meester, Verspuy, Monsieurs, & Van Bogaert, 2013;Radtke, 2013;Townsend-Gervis, Cornell, & Vardaman, 2014), the impact of different models of care on communication (Fernandez, Tran, Johnson, & Jones, 2010), communication technologies (Guarascio-Howard, 2011) and factors that impair communication (Johnson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%